KEMAMPUAN PELAKSANAAN FUNGSI DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN MINAHASA UTARA - DENDENG, FERJENIA; DENGO, SALMIN; LONDA, VERY (Sam Ratulangi University, 2020)
The purpose of this study is to explain the ability to carry out the functions of the people’s RespresentativeCouncil of north Minahasa Regency The research concept used in this research is to use this type ofresearch by participant observation, in-depth interviews, and documentation studies. The result of thestudy concluded that functions of the people’s Respresentative Council of North Minahasa Regency hasnot been well achieved because of the lack of understanding of the members of the council on thetechnical work much helped by the support of staff and experts, in desicion-making faction based on theparty’s instructions, members of the council have not been able to adapt well to work relations as thefunction of the council, and are less able to criticize the RAPBD and the oversight function is not workingproperly. So it can be concluded tha ability of the board members functions is not maximal or optimal.Keywords :Ability, Implementation, Function